The phenomenological inquiry: tool for approaching architectural design learning - Linares, Maria Auxiliadora (Universidad de Boyacá, 2017)
This paper is derived from systematized inquiries related to the academic praxis and the concern for guiding the students of the Architectural Design Workshop of the University of Zulia, Venezuela, to innovative research strategies in their learning process. The starting point are the variables associated to the complexity of the discipline as a science that enables human actions in living spaces. Phenomenology represents a valuable tool for such a complexity as it may support students in questioning during their learning process as well as in their professional work. From a hermeneutical analysis on the postulates of authors such as Bachelard, Husserl and Van Manen, the contribution of the phenomenological method to architectural learning is identified. Phenomenological instruments such as interviews, recording of particular cases and field observations allowed to know experiences from inhabitants of some places. Such experiences served as experiential information to be studied. Professors of Architectural Design Workshop may find in inquiring and the phenomenological description a direction for the academic approach of the architectural space design.